Another age another time - "Sahay, S" (New Delhi, 1999)
Journalism is a jealous mistress, as those who came under its spell,even the reluctant ones, like the author, discover. It ultimately consumes you. There is nothing like a half-hearted journalist. Despite its transitoriness, its accent on living from moment to moment, it imposes its own discipline and sets of values. there are few other professions in the world in which everybody's business in your business, in which you vicariously share the triumphs and tragedies of others as if it were your own, and in which you work for a particular editon or "story", as if your life depended on it, and then coolly move on to the next "beat" or subject.
Keywords: Mass media